Protective Effects of Dl-Limonene Alone and Combination With 6-Methyleneandrosta-1, 4-Diene-3, 17-Dione against Mammary Carcinoma Induced Female Albino Rat - Ojedapo, GC; Minari, JB; Oloyede, AM (Chemistry and Biochemistry: Research Progress Vol. 2, 2025)
Breast cancer is a serious prime hassle commonly diagnosed in women and the second most prevalent cause of cancer-related mortality. A better understanding of these changes and their accompanying molecular signaling networks opens the door to new therapeutic options. Chemotherapy is one of the most widely used therapies; however, due to the unpleasant side effects and multidrug resistance that patients may develop, substantial progress has been made in the quest for novel options, such as the use of plant-derived natural chemicals. Many bioactive chemicals derived from plants have been reported to have anticancer properties and possess the potential to decline and alter the upshots of chemotherapy drugs in most breast cancer treatments. Limonene is a chemical compound found in the rind of citrus fruits such as lemon and orange. Limonene is broadly used in soft drinks, cosmetics, and numerous other seasoning products. Given its unexpectedly increasing operations in the synthetic and food sectors as a result of its excellent cologne rates, Previous studies have determined that each D and L-limonene has a useful anticancer impact on a variety of cancers, but the effects and the risk associated with the use of a race mixture of this limonene at 1:1 have not been ascertained. The purpose of this study is to look into the potential and risks of a racemic mixture of DL limonene (1:1) and its combination with 6-Methyleneandrosta-1, 4, Diene-3, 17-dione in NMU and Estradiol-induced female rats. Ninety (90) female albino rats at seven weeks of age were used for this study. Powdered food was supplemented with DL-limonene to achieve a final limonene concentration of 5% to 10% and 6-Methyleneandrosta-1, 4, Diene-3, and 17-dione were given to each rat by subcutaneous injection thrice in a week. To determine the ameliorative alteration of tumours in the induced female rat, tumour assessment was employed using a vernier caliper, haematological parameters were analyzed using an automated blood analyzer. To assess the safety and efficacy of dl-limonene and its combination with 6-ADD, biochemical assessment and enzymatic antioxidants were employed using standard protocols, while hematoxylin and eosin were used for histological assays. Thus the results obtained from this study clearly indicate that DL-limonene alone and its combination with 6- ADD at 5% and 12.5 mg/kg significantly suppresses and ameliorates the alteration of NMU and estradiol-induced breast cancer in rats.